Investigating Catalytic Properties of Nanoferrites for Both AP and Nano-AP Based Composite Solid Propellant. Issue 13 (3rd October 2021) - Vara, Jalpa A; Dave, Pragnesh N.; Chaturvedi, Shalini
ABSTRACT: In this paper, the comparison studies of nanoferrites catalytic efficiency for thermal behavior of AP and nano-AP (NAP)-based CSPs were investigated. A co-precipitation procedure was used for the preparation of nanoferrites (CuNiF, CoMnF, and NiZnF) and NAP was synthesized using a non-aqueous method. XRD, FTIR, and SEM instruments were utilized for characterization of nanoferrites and NAP. The catalytic efficiency of nanoferrites on the thermal behavior of AP- and NAP-based CSPs was investigated by using TG-DSC technique. The KAS, FWO, and Starink methods were applied to estimate activation energies of AP- and NAP-based CSPs samples. Nanoferrites showed good catalytic efficiency on AP- and NAP-based CSPs that reduced the decomposition temperature and activation energy of AP- and NAP-based CSPs. The NAP-based CSPs with nanoferrites is more precious than AP-based CSPs with nanoferrites.